Maxwell Hybrid Nanofluid (Cu-Al2O3/Water) and (CuO-Ag/Water) Near a Stagnation Point above an Extending Sheet (European Journal of Pure and Applied Mathematics, 2025)
This article investigates Maxwell hybrid nanofluids (Cu-Al2O3/water and CuO-Ag/water) at a stagnation point over an extended sheet. The issue is motivated by its potential importance in enhancing thermal efficiency in modern heat transfer applications, crucial in optimizing manufacturing processes and energy conservation technology. Therefore, the present study investigates a non-Newtonian Maxwell nanoliquid across a mixed convection boundary layer (BL) and heat broadcast past a shrinking/stretching surface containing hybrid nanoparticles. In the current work, two different kinds of hybrid nanofluids are involved: Cu-Al2O3/water and CuO-Ag/water. Copper particles (Cu) and Copper oxide particles (CuO) are mixed into an Al2O3/water and Ag/water nanofluid to study these two types. The flow is acted upon the impact of a uniform magnetic field(MF) and a stagnation point. The issue arises from their enhanced thermal conductivity and heat transfer capabilities, which are crucial for enhancing energy efficiency in advanced cooling systems and engineering applications involving stagnation point flows. By utilizing suitable transformations, the partial differential equations (PDEs) are transformed into ordinary differential equations (ODEs). The prototype undergoes computational analysis utilizing the fourth-order Runge-Kutta (RK-4) method in conjunction with the shooting technique. The outcomes of the current work have applicable importance concerning the stagnation point flow, like cooling of nuclear reactors, cooling of microelectronic procedures by supporters, wire drawing, polymer extrusion, and many engineering hydrodynamic applications. The influences of the picked factors on the temperature, velocity, heat transmission rate, and skin friction factor are theoretically and numerically investigated. It is found that the existence of different hybrid nanoparticles with the influences of other parameters plays a significant role in both the velocity and temperature distributions. Additionally, the stagnation point creates a separation limit in the liquid flow that reverses the magnetic field influence between these flow regions.
Keywords: Hybrid nanofluid; Non-Newtonian Maxwell fluid; Stagnation point; Stretching surface; Magnetohydrodynamics.